Synthesis, characterization, and biological properties of composites of hydroxyapatite and hexagonal boron nitride - OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; KILIÇ, OSMAN; ÜNAL YILDIRIM, SEMRA (WILEY, 2018)
Hydroxyapatite (HA), obtained from bovine bones, was successfully reinforced with hexagonal boron nitrite (h-BN). h-BN/HA composites, with BN content up to 1.5 wt %, were sintered at various temperatures between 1000 and 1300 degrees C, in air. Well-sintered samples were obtained after sintering at 1200 and 1300 degrees C. The presence of h-BN contributed to dense, fine, and well-crystallized microstructure. The results of X-ray diffraction analysis and FT-IR spectroscopy showed that the produced composites comprised biphasic beta-TCP/HCA (HCA: carbonate partially substituted HA). High values of mechanical properties were achieved, namely compression strength 155 MPa for the sample 0.5% h-BN/HA and Vickers microhardness of 716 HV for the samples 1.5% h-BN/HA, both sintered at 1300 degrees C. U2OS human bone osteosarcoma proliferation and cell viability showed no adverse effect in the presence of h-BN/HA, suggesting the potential use of the produced materials as safe biomaterials in bone tissue engineering. (C) 2017 Wiley Periodicals, Inc.
Keywords: composites; hydroxyapatite; bovine bone; hexagonal boron nitride; bioceramic; MECHANICAL-PROPERTIES; SINTERING TEMPERATURE; APATITE; NANOPARTICLES; NANOTUBES; BHA